Women In Climate Change Programs: The Trap of Neoliberal Culture Through Economic Empowerment - Hidayat, Rahmat; Nutfa, Moh; Ariyani, Risma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Women's economic empowerment in the forestry sector development program in Oo Village, South Kulawi District, Sigi Regency, Central Sulawesi Province through the Reduces Emissions from Deforestation and Forest Degradation (REDD+) scheme in the Sulawesi Forest Program III project funded by the German government, not just a project environment driven by the moral and humanitarian awareness of community guardians to save the environment while empowering the economy of rural women. REDD+ as a program actually, through its empowerment work, has other implications, namely its contribution to the fading of the traditional subsistence cultural value system in the Oo Village community. In socio-cultural conditions that have faded due to the pressure of modernization in the forestry sector, the presence of the REDD+ program with all its rules, such as encouraging women to independently develop their economy through stabilizing land use, instead of empowering women economically, this research sees that Empowerment through land use regulation within the framework of environmental saving projects actually traps women into a neoliberal cultural value system.